HLA Class II Molecules Influence Susceptibility vs Protection in Inflammatory Diseases by Determining the Cytokine Profile - Mangalam, Ashutosh K. (2013)
The MHC in humans encodes the most polymorphic genes, the HLA genes, which are critical for the immune system to clear infection. This can be attributed to strong selection pressure as populations moved to different parts of the world and encountered new kinds of infections, leading to new HLA class II alleles. HLA genes also have the highest relative risk for autoimmune diseases. Three haplotypes—HLA-DR2DQ6, DR4DQ8, and DR3DQ2—account for HLA association with most autoimmune diseases. We hypothesize that these haplotypes, along with their multiple subtypes, have survived bottlenecks of infectious episodes in human history because of their ability to present pathogenic peptides to activate T cells that secrete cytokines to clear infections. Unfortunately, they also present self-peptides/mimics to activate autoreactive T cells secreting proinflammatory cytokines that cause autoimmune diseases.